Analysis of the Implementation of Responsible Character in Online Learning During the Covid-19 Pandemic: Analisis Implementasi Karakter Tanggung Jawab dalam Pembelajaran Daring di Masa Pandemi Covid-19 - Dewi Noviastuti Novi; Muhlasin Amrullah (Universitas Muhammadiyah Sidoarjo, 2022)
This meta-analysis investigates the implementation of student responsibility in online learning during the COVID-19 pandemic. By conducting a comprehensive literature review, relevant articles, journals, and references were analyzed to explore the challenges posed by the pandemic on education. The results highlight a decline in student responsibility and engagement in online learning, manifested through incomplete assignments and reduced participation. To address these issues, character education emerges as a potential solution, emphasizing the collaboration between teachers, students, and parents. This study sheds light on the importance of fostering student responsibility and suggests implications for educators and policymakers to enhance the online learning experience amidst global crises. Highlights: The COVID-19 pandemic has disrupted traditional face-to-face learning, necessitating a shift to online learning. Online learning has posed challenges to student responsibility, with decreased engagement and incomplete assignments. Implementing character education in collaboration with parents can help foster student responsibility in online learning. Keywords: COVID-19, online learning, student responsibility, character education, meta-analysis